STUDI ETNOFARMASI TUMBUHAN BERKHASIAT OBAT PADA SUKU GORONTALO DI KECAMATAN POPAYATO TIMUR KABUPATEN POHUWATO PROVINSI GORONTALO - Andi Atirah Masyita; Nurlina Ibrahin; Fitri Rahayu (Melati Institute, 2023)
The Gorontalo tribe in East Popayato District is one of the tribes in Gorontalo Province who believe in traditional medicine using medicinal plants. This study aims to obtain the knowledge and skills possessed by traditional healers in East Popayato District, Pohuwato Regency, types of plants and plant parts used as medicine and processing methods, methods of use, dosage, rules of use and duration of use ordered to treat a disease by Gorontalo tribe. This type of research is descriptive research using qualitative methods with a sampling technique that is purposive sampling, through semi-structured interviews with 10 hattra. Results Based on the research, there are 37 types of plants used as medicine. The most widely used plant parts are leaves with a percentage of 56%, other parts are stems 6%, fruit 9%, rhizome 6%, seeds 2%, bark 4%, tubers 2%, roots 9%, latex 4%, and 2% interest. As for how to treat plants, it is done by serving with a percentage of 51%, pounded 18%, brewed 9%, kneaded 4%, scraped 6%, shredded 6%, and soaked as much as 6%. The way to use it is by drinking 64%, smearing 8%, dripping 4%, bathing 11%, gargling 2%, and sticking 11%. The duration of treatment is 3-14 days. Diseases to be treated include kidney failure, post-natal health, phlegm, bad breath, hemorrhoids, measles, asthma, malaria, tuberculosis, heartburn, stroke, liver disease, urinary stones, vaginal discharge, ingrown toenails, cancer, acne, cholesterol, pain. teeth, rheumatism, diarrhea, wounds, diabetes, hypertension, cough, ulcers, and gout.